System identification and position control of pneumatic actuator using embedded system - Ahmed Sadeq, Taha Mohammed (2015)
This project report presents the ability of using embedded system to control non-linear systems like pneumatic actuators. The pneumatic actuators are commonly used in industrial applications because they have many practical advantages such as high power to weight ratio and cheap compared to other actuators. Embedded system STM32F4DISCOVERY was used in this project to interface the pneumatic actuator with MATLAB® Simulink instead of using the conventional Data Acquisition card (DAQ) to reduce the cost and size. The embedded system was also used as a controller to execute the control algorithms. The model of the pneumatic actuator was identified by using system identification technique. Based on this model, the Proportional-Integral-Derivative (PID) and the Proportional-Derivative Fuzzy Logic (PD-Fuzzy) controllers were designed to control the position of the pneumatic actuator. Waijung Blockset in MATLAB® Simulink was used to estimate the model of the pneumatic actuator and implement these controllers inside the embedded system STM32F4DISCOVERY. A Pneumatic Actuated Ball and Beam System (PABBS) is an application of controlling the position of the pneumatic actuator. The developed model of PABBS was used to design three controllers for this plant based on the controllers of the pneumatic actuator. The Cascade PID, the PD-Fuzzy with Gain Feedback and the PD-Fuzzy with PID controllers were designed to control the ball at the desired position. For the position control of the pneumatic actuators, the simulation and experimental results of the PID and PD-Fuzzy controllers were presented. The PD-Fuzzy offers better control compared to other controllers in terms of stability and robustness for the pneumatic actuator. On the other hand, PD-Fuzzy with PID controllers gave the best control response in the simulation compared to the others controllers for the PABBS application.